ADHESION OF BIOCOMPATIBLE TiNb COATING - Tomas Kolegar; Martin Matousek; Monika Vilemova; Vladimir Stary (Acta Polytechnica CTU Proceedings)
Preparation of a coating with a high quality requires good adhesion of the film to the substrate. The paper deals with the adhesion of biocompatible TiNb coating with different base materials. Several materials such as titanium CP grade 2, titanium alloys Ti6Al4V and stainless steel AISI 316L were measured. Testing samples were made in the shape of small discs. Those samples were coated with a TiNb layer by using the PVD method (magnetron sputtering). Onto the measured layer of TiNb an assistant cylinder was stuck using a high strength epoxy adhesive E1100S. The sample with the assistant cylinder was fixed into a special fixture and the whole assembly underwent pull-off testing for adhesion. The main result of this experiment was determining the strength needed to peel the layer and morphology and size of the breakaway. As a result, we will be able to determine the best base material and conditions where the coating will be remain intact with the base material.